2015
DOI: 10.1139/cjc-2015-0025
|View full text |Cite
|
Sign up to set email alerts
|

Structure, vibrational spectroscopy, and photochemistry of 5-phenoxy-1-phenyltetrazole in argon and nitrogen cryomatrices

Abstract: The molecular structure, infrared spectra, and photochemistry of 5-phenoxy-1-phenyltetrazole (5PPT) isolated in argon and N 2 cryogenic matrices were investigated by infrared spectroscopy and theoretical calculations (DFT(B3LYP)/6-311++G(d,p)). Calculations yield two dissimilar minima on the potential energy surface of the molecule, both being eightfold degenerate by symmetry and belonging to the C 1 symmetry point group. Extensive analysis of the potential energy landscape of the molecule was performed. Upon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 42 publications
1
0
0
Order By: Relevance
“…These conclusions were confirmed through the experimental photolysis studies in which preferential cleavage through pathway A (Scheme 4) was observed for these compounds and further corroborated by the ∆G values calculated for each pathway [21,38]. Calculated energies of 5-phenoxy-1-phenyltetrazole and its photoproducts, at the same level of theory, were in agreement with the experimental results of the photochemically induced cleavage [42], emphasising the importance of such calculations in these type of studies.…”
Section: Theoretical Studiessupporting
confidence: 78%
“…These conclusions were confirmed through the experimental photolysis studies in which preferential cleavage through pathway A (Scheme 4) was observed for these compounds and further corroborated by the ∆G values calculated for each pathway [21,38]. Calculated energies of 5-phenoxy-1-phenyltetrazole and its photoproducts, at the same level of theory, were in agreement with the experimental results of the photochemically induced cleavage [42], emphasising the importance of such calculations in these type of studies.…”
Section: Theoretical Studiessupporting
confidence: 78%